PENGARUH KEPUASAN KERJA, PENGEMBANGAN KARIER DAN KOMPENSASI TERHADAP LOYALITAS PEGAWAI DINAS PARIWISATA KOTA YOGYAKARTA - Prayekti, Prayekti; Hadi, Syamsul; Hendriawan, Apit (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Employees play an important role in the success of an organization. Thus, organizations are claimed to have skilled human resources that are committed to their work. As for the purpose of this study to find out the impact of job satisfaction, career development, and compensation on employee loyalty. This research approach uses a quantitative approach. The population in this study of 71 people represents the entire workforce of Yogyakarta City Tourism Service, including people who occupy various positions and responsibilities. The sampling technique is a saturated sample. Research data collection methods using quioner methods. Data analysis techniques using double linear regression analysis techniques. The t test is used to test partial influences. The results of the research concluded that job satisfaction has a positive impact on employee loyalty; career development has a positively impacted employee loyality; compensation positively affects employee lojality; and simultaneously employment satisfaction, career development and compensation have a positive effect on employees loyalty. This research advises employees to increase job satisfaction, and encourage employees to advance their careers, as well as rationalize compensation. The officers should be able to work professionally and earnestly